1983
DOI: 10.1007/bf01656143
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral versus bilateral adrenalectomy in multiple endocrine neoplasia IIA

Abstract: Factors influencing the result of various forms of surgical treatment for pheochromocytoma were studied in patients with multiple endocrine neoplasia IIA (MEN IIA) syndrome. The material consisted of 18 patients belonging to 4 non‐related families operated on during 1966–1981 with a mean follow‐up time of 7.4 years. Twenty‐seven adrenals were removed at 22 operations. In all adrenals, multiple pheochromocytomas and/or medullary hyperplasia were present. In 13 patients the first operation was a unilateral adren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 13 publications
1
17
0
1
Order By: Relevance
“…Data on recurrent pheochromocytoma after adrenalsparing adrenalectomy were given in 15 studies. 3,7,[9][10][11][12][13][14][15][16][17][18]20,22,23 Fifty-eight (31%) of 187 patients developed a recurrent pheochromocytoma in either the ipsilateral or contralateral adrenal remnant. The interval to developing recur- rent disease was a median of 83.5 months (range, 1-375 months).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Data on recurrent pheochromocytoma after adrenalsparing adrenalectomy were given in 15 studies. 3,7,[9][10][11][12][13][14][15][16][17][18]20,22,23 Fifty-eight (31%) of 187 patients developed a recurrent pheochromocytoma in either the ipsilateral or contralateral adrenal remnant. The interval to developing recur- rent disease was a median of 83.5 months (range, 1-375 months).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Some authors have no experience of malignant pheochromocytomas [6,7]; however, van Heerden et al reported 3 cases of metastatic pheochromocytoma in their 17 patients [5], and there is an another report of a malignant case [13]. Thompson et al detected metastatic pheochromocytomas in 2 out of 8 patients with MEN 2A using 131J MIBG scans [14].…”
Section: Outcome Of Adrenal Autotrans Plantationmentioning
confidence: 99%
“…Hypertension remained in three patients, though they underwent total adrenalectomy in either one-or two-stage operation. [5,11]; however, others have expressed a different opinion about the prophylactic removal of a macroscopically normal adrenal at the same time of operation for resecting obvious pheochromocytoma on the other side [6][7][8]. Tibblin et al have recommended unilateral adrenalectomy when the largest diameter of the biggest tumor is less than 5 cm and the contralateral side is grossly normal by palpation [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hauptargument der überwiegend vom angloamerikanischen Raum ausgehenden Strategie der bilateral totalen Adrenalektomie war das krankheitsimmanente Rezidivrisiko. Nach ersten Publikationen zur funktionserhaltenden Adrenalektomie durch Tibblin [2] …”
unclassified